THE COMPARISON OF OUTSOURCING SYSTEM ARRANGEMENTS BETWEEN INDONESIA AND SINGAPORE - Kurniawati L.; Budiono A.R.; Permadi I.; Safa’at R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
In Indonesia, the system of outsourcing work is not a recent development. Contract labor has really been used in numerous plantations on the islands of Java and Sumatra since the Dutch colonial era to execute this system. When the New Order administration was in power, outsourcing was implemented by offering rewards for making it easier for businesses operating in unionized areas to obtain business licenses (export processing zones). Many nations have long used a variety of models to practice the working relationship with outsourcing. In contrast, it is practically quite similar to Indonesia's employment relationship practice of the charter. Unquestionably, this kind of work practice is now required. Singapore is a developed nation in Asia, particularly Southeast Asia, with effective labor laws. Singapore's judicial system treats its residents with a decent amount of impartiality and fairness. The Singapore Employment Act, the Immigration Act, and the Labor Guidelines are only a few of the laws that regulate foreign employees in all ways. Only the Philippines and Indonesia in Asia have severe limitations on the use of contracting and outsourcing. The research's methodology is normative juridical, with the philosophical, comparative, and historical manner of approaching law. In order to execute outsourcing procedures without causing controversy, especially if it is harmful to workers/labor, there are a number of conditions that must be met. This is true for both Singapore and Indonesia. Improving the quality of the workforce, tough law enforcement against infractions, ensuring easy access to the labor market, and providing social protection mechanisms for workers/laborers who are not absorbed in the labor market must all be done in conjunction with the practice of outsourcing. Additionally, it's crucial to consider the bargaining position between groups of companies and labor unions, especially when negotiations take place at the corporate level.